PENGARUH TEKNIK KANCING GEMERINCING TERHADAP HASIL BELAJAR SISWA KELAS V SDN 10 MATARAM PADA MUATAN IPS TAHUN PELAJARAN 2019/2020 - Hilma Yuliana; Nasruddin Nasruddin; Itsa Oktaviyanti; Nurhasanah Nurhasanah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the effect of Kancing Gemerincingtechnique to the students learning outcomes on social science of fifth grade at elementary school 10 Mataram in school year 2019/2020. This type of research was an experimental research of Quasi-Experimental Design type Nonequivalent type Control Group Design. The population in this study was all fifth grade students of elementary school 10 Mataram. The sampling technique used was saturated samples. The Data collection techniques in this study used was test for social science data of students learning outcomes which previously have tested the validity and reliability. Testing requirements analysis using was normality and homogeneity test. The data analysis technique used was the t-test analysis using polledvariance. From the calculation results obtained t ≥ t table that is equal to 3.322 ≥ 1.994 at significance level of 5% (0.05) with degrees of freedom (df) = n1 + n2 - 2 = 36 + 37-2 = 71. In accordance with hypothesis testing criteria, if t count ≥ t table, then H0 is rejected and Ha accepted. it shows that there are significant effect of Kancing Gemerincing technique to the students learning outcomes on social science of fifth grade at elementary school 10 Mataram in school year 2019/2020.